First-Trimester Biochemical Inflammatory Markers (NHR and NLR) as Predictors of Preeclampsia Risk: First-Trimester Biochemical Markers for Preeclampsia - Wang, Qianqian; Li, Xuehui; Ma, Xiaotao Ma (Journal of Medical Biochemistry, 2025)
Background: Preeclampsia (PE) remains a leading cause of maternal and perinatal morbidity. Early identification of high-risk pregnancies requires accessible and cost-effective laboratory markers. This study aimed to evaluate first-trimester blood count–derived inflammatory indices, with a focus on the neutrophil-to-HDL ratio (NHR) and neutrophil-to-lymphocyte ratio (NLR), for PE risk prediction.Methods: Ninety patients with PE and 90 healthy pregnant women were retrospectively analyzed. Routine hematological and biochemical parameters were measured using an automated biochemical analyzer, and derived indices (NLR, NHR, MHR, SII) were calculated. Independent risk factors were determined through multivariate logistic regression, and a predictive model was validated by receiver operating characteristic (ROC) curve analysis.Results: PE patients exhibited significantly higher NLR, NHR, and SII compared with controls (all p < 0.001). Logistic regression identified NLR, NHR, and body mass index (BMI) as independent predictors of PE. The combined model incorporating these factors achieved excellent predictive performance, with an area under the ROC curve of 0.909 (95% CI: 0.866–0.952).Conclusion: First-trimester laboratory indices, particularly NHR and NLR, provide reliable biochemical markers for early PE risk assessment. The proposed laboratory-based model may facilitate cost-effective screening, improve risk stratification, and support preventive strategies in clinical practice.
Keywords: preeclampsia; neutrophil-to-HDL ratio; neutrophil-to-lymphocyte ratio; laboratory markers; biochemical indices; early prediction